Differences in pulmonary and extra-pulmonary traits between women and men with chronic obstructive pulmonary disease - Souto-Miranda, Sara (2022)
Background: Evidence suggests sex-related differences in chronic obstructive pulmonary disease (COPD). Whether these differences are reflected in the prevalence of treatable traits remains unknown. Methods: Two samples of patients referred to secondary (n = 530) or tertiary care (n = 2012) were analyzed. Men and women were matched for age, forced expiratory volume in 1 s and body mass index. Sex-related differences were tested using t-tests, Mann-Whitney U, or chi-square tests. Results: Frequent exacerbations (30.5 vs. 19.7%), high cardiovascular risk (88.1 vs. 66.2%) and activity-related severe dyspnea (50.9 vs. 34.8%) were more prevalent in women in secondary care (p < 0.05). Severe hyperinflation (43.0 vs. 25.4%), limited diffusing capacity (79.6 vs. 70.1%), impaired mobility (44.0 vs. 28.7%), frequent exacerbations (66.8 vs. 57.4%), frequent hospitalizations (47.5 vs. 41.6%), severe activity-related dyspnea (89.1 vs. 85.0%), symptoms of anxiety (56.3 vs. 42.0%) and depression (50.3 vs. 44.8%), and poor health status (79.9 vs. 71.0%) were more prevalent in women in tertiary care (p < 0.05). Severe inspiratory muscle weakness (14.6 vs. 8.2%) and impaired exercise capacity (69.1 vs. 59.6%) were more prevalent among men (p < 0.05) in tertiary care. Conclusions: Sex-related differences were found, with most traits more prevalent and severe among women. Care providers should be aware of these differences to adjust treatment.